Karstification of interior Eyre Peninsula, South Australia and its impacts on land use. Issue 2 (2nd July 2016) - Bourne, J. A.; Twidale, C. R.
ABSTRACT: An extensive and composite field of calcareous coastal foredunes was deposited on the west coast of Eyre Peninsula during the Middle and Late Pleistocene. Several islands became linked to the mainland. Rivers that previously had drained to the Great Australian Bight were blocked and their valleys alluviated. The dunes became the source of successive transgressive sand sheets forming extensive lobes of calcarenites, which covered the pre-existing landscape. Weathering released calcareous dust to be carried by westerly winds and spread over the riverine plains and later to be consolidated as calcrete. Thus was created the present streamless karst landscape. The calcrete also helped stabilise the field of Late Pleistocene desert dunes that extended southeastwards over the interior plains. Early farming practices and settlement were affected profoundly by these changes in the natural environment, as are their modern successors.